Friend or foe? Inflammation and the foreign body response to orthopedic biomaterials - Gibon, Emmanuel; Takakubo, Yuya; Zwingenberger, Stefan; Gallo, Jiri; Takagi, Michiaki; Goodman, Stuart B (Journal of biomedical materials research. Part A, 2024)
The use of biomaterials and implants for joint replacement, fracture fixation, spinal stabilization and other orthopedic indications has revolutionized patient care by reliably decreasing pain and improving function. These surgical procedures always invoke an acute inflammatory reaction initially, that in most cases, readily subsides. Occasionally, chronic inflammation around the implant develops and persists; this results in unremitting pain and compromises function. The etiology of chronic inflammation may be specific, such as with infection, or be unknown. The histological hallmarks of chronic inflammation include activated macrophages, fibroblasts, T cell subsets, and other cells of the innate immune system. The presence of cells of the adaptive immune system usually indicates allergic reactions to metallic haptens. A foreign body reaction is composed of activated macrophages, giant cells, fibroblasts, and other cells often distributed in a characteristic histological arrangement; this reaction is usually due to particulate debris and other byproducts from the biomaterials used in the implant. Both chronic inflammation and the foreign body response have adverse biological effects on the integration of the implant with the surrounding tissues. Strategies to mitigate chronic inflammation and the foreign body response will enhance the initial incorporation and longevity of the implant, and thereby, improve long-term pain relief and overall function for the patient. The seminal research performed in the laboratory of Dr. James Anderson and co-workers has provided an inspirational and driving force for our laboratory's work on the interactions and crosstalk among cells of the mesenchymal, immune, and vascular lineages, and orthopedic biomaterials. Dr. Anderson's delineation of the fundamental biologic processes and mechanisms underlying acute and chronic inflammation, the foreign body response, resolution, and eventual functional integration of implants in different organ systems has provided researchers with a strategic approach to the use of biomaterials to improve health in numerous clinical scenarios.
Keywords: reakce na cizí těleso; biokompatibilní materiály; Biocompatible Materials; zánět; lidé; Animals; ortopedie; Orthopedics; protézy a implantáty; Humans; Inflammation; Prostheses and Implants; zvířata; Foreign-Body Reaction